2023
DOI: 10.1136/jech-2023-220337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urban and rural mortality rates across the lifespan in Aotearoa/New Zealand: a population-level study

Abstract: BackgroundPrevious studies undertaken in New Zealand using generic rurality classifications have concluded that life expectancy and age-standardised mortality rates are similar for urban and rural populations.MethodsAdministrative mortality (2014–2018) and census data (2013 and 2018) were used to estimate age-stratified sex-adjusted mortality rate ratios (aMRRs) for a range of mortality outcomes across the rural-urban spectrum (using major urban centres as the reference) for the total population and separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…The lower rural vaccination rates observed among younger age groups align with similar recent concerning findings. Relative to their urban peers, younger rural dwellers had lower rates of utilization of key secondary care services [ 27 ], but inversely higher rates of all-cause, amenable, and injury-related mortality [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower rural vaccination rates observed among younger age groups align with similar recent concerning findings. Relative to their urban peers, younger rural dwellers had lower rates of utilization of key secondary care services [ 27 ], but inversely higher rates of all-cause, amenable, and injury-related mortality [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…By December 2021, the rural-urban uptake gradient was less pronounced in Te Waipounamu, whereas differences in uptake rates between the most remote (R3) and most urban (U1) communities were most marked in the Northern region. While further research is required to understand the drivers of these differences, they could relate to regional geography, sociodemographic differences in rural communities by region [28,29], differing approaches to regional vaccination roll-outs, and regional differences in the accessibility of vaccination services including the intermittent nature of 'mobile' rural clinics [16,30].…”
Section: Epidemiology and Infectionmentioning
confidence: 99%
“…These findings suggest that rural populations tend to have higher mortality rates than those in urban settings. 1 - 7 Using data from the National Vital Statistics System, a large US study revealed an important increase in the age-adjusted mortality rate in rural areas, which was only 7% higher than in urban centers in 1999, but 20% higher in 2019. 1 However, this and most other studies from High Income Countries failed to focus on the many risk factors that contributed to the greater mortality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the role of individual risk factors on all-cause mortality was often unrecognized. 1 - 4 …”
Section: Introductionmentioning
confidence: 99%
“…7 Mortality disparities identified by the GCH differ considerably across age bands, with younger rural residents having higher mortality rates than their urban peers, but older rural residents having mortality rates similar to or slightly lower than their urban peers. 8 Rural Māori have consistently poorer health outcomes than rural non-Māori, frequently exceeding the ethnic inequities observed in the urban context. 9 In June 2022, New Zealand's parliament passed into law the Pae Ora (Healthy Futures) Bill.…”
mentioning
confidence: 99%